Применение теории игр в управлении it-проектами - Паскарюк, Д. О. (ХНУРЕ, 2019)
This work describes an approach for finding optimal strategies of solving project management problems in Scrum methodology. Finding the right strategy is quite a challenge due to the large number of different human and technical factors. In order to find the optimal project management strategy is proposed to use the game theory. This theory allows to build a step by step solution of existing problems spending a minimum of time.